1987
DOI: 10.1136/jramc-133-02-10
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Spondylolysis – A Case Reports

Abstract: The repeated minor stress of sport can produce a fatigue fr actu re of the neural arch. A case of unilateral spondylolysis progressing to bilateral defects and developing spondylolisthesis is described. A review of the literature is presented and the aetiology of spondylolysis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the clinical literature, spondylolysis has been associated with activities that involve repetitious, vigorous exercise, such as gymnastics (Jackson et al, 1976;Goldberg, 1980;Hooper, 1984;Ciullo and Jackson, 1985;Bozdech and Dukek, 1986;Letts et al, 1986;Commandre et al, 1988), contortionism (Steinbuck and Springorum, 1980), dancing (Micheli, 1983;Bejjani, 1987), diving (Rossi and Dragoni, 1990), hockey (Letts et al, 19861, javelin throwing (Feldmeier et al, 1985;Bejjani, 1987;Chapman, 1987), rowing (Stallard, 1980), canoeing (Jakab, 1989), football (Ferguson et al, 1974;Alexander, 1985;McCarroll et al, 1986), handball (Hoshina, 1980), weight lifting (Kotani et al, 1971;Granhed and Morelli, 1988;Risser, 1991), and wrestling (Rossi and Dragoni, 1990).…”
Section: Discussionmentioning
confidence: 97%
“…In the clinical literature, spondylolysis has been associated with activities that involve repetitious, vigorous exercise, such as gymnastics (Jackson et al, 1976;Goldberg, 1980;Hooper, 1984;Ciullo and Jackson, 1985;Bozdech and Dukek, 1986;Letts et al, 1986;Commandre et al, 1988), contortionism (Steinbuck and Springorum, 1980), dancing (Micheli, 1983;Bejjani, 1987), diving (Rossi and Dragoni, 1990), hockey (Letts et al, 19861, javelin throwing (Feldmeier et al, 1985;Bejjani, 1987;Chapman, 1987), rowing (Stallard, 1980), canoeing (Jakab, 1989), football (Ferguson et al, 1974;Alexander, 1985;McCarroll et al, 1986), handball (Hoshina, 1980), weight lifting (Kotani et al, 1971;Granhed and Morelli, 1988;Risser, 1991), and wrestling (Rossi and Dragoni, 1990).…”
Section: Discussionmentioning
confidence: 97%
“…25 As the most commonly suspected etiologic component of spondylolysis is stress (fatigue) fracture of the pars interarticularis, 1 the relationship between spondylolysis and military parachutists is supported by the repetitive heavy axial compression and twisting of the spine associated with landing. 26,27 In a radiographic study of the lumbar spine in military parachuting instructors (N = 74) having performed an average of 410 jumps, Bar-Dayan et al 28 concluded that parachuting predisposes to spondylolysis and to degenerative changes of the lumbar spine.…”
Section: Discussionmentioning
confidence: 99%